Problems of Tolerance and Adaptability of Personality in Polycultural Society - S I Kudinov; S S Kudinov (Peoples' Friendship University of Russia (RUDN University), 2014)
The results of the empirical research on the relationship of tolerance and adaptability of the students belonging to different ethnic groups and cultures are analyzed in the article. The comparative analysis of the adaptability in the respondents with high and low tolerance levels is carried out.